THE VIEWS OF THOMAS AQUINAS UPON THE PROBLEM OF SENSE OF LIFE - Кравченко, В. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the Thomas Aquinas ethical conception of sense of life through the synthesis of classical ancient Greek philosophy and Christian theology.